HUBUNGAN GAMBARAN USG GINJAL DENGAN GEJALA KLINIS KOLIK ABDOMEN PADA PENDERITA NEFROLITIASIS - Purba, Lenny Sapitry; Damanik, Irene R.T; Nainggolan, Renatha (Jurnal Kedokteran Methodist, 2021)
Background : In Indonesia, kidney disease which is quite common is nephrolithiasis, with a prevalence of 0.6%. As a result of stones located in the kidney will appear symptoms of colic pain, hematuria, nausea and vomiting and stone discharge when urinating. Ultrasound examination should be used as the main radiological examination, this examination is very effective in detecting the location and size of stones in the kidney area. The purpose of this study was to determine the relationship between renal ultrasound images and clinical symptoms of abdominal colic in patients with nephrolithiasis. Methods: : The research method used is Literature Review, using secondary data. Data were collected using documentation techniques. The research journals used were 7 journals with inclusion criteria of publication date of the last 5 years, the language used was Indonesian or English, with the research subjects being patients with a diagnosis of nephrolithiasis. Conclusion: Based on the research that has been done, there is a relationship between the ultrasound picture of the kidneys and the clinical symptoms of abdominal colic in patients with nephrolithiasis.